Democratic Decentralization and the Marginalized: The Case of Scheduled Tribes in Kerala - Surjith .M (KILA Journal of Local Governance, 2015)
The major argument in favor of democratic decentralization had been that it multiplies the participation possibilities of traditionally marginalized segment of the population, and to effectively negotiate with local democratic institutions. However, neither the theoretical studies nor the empirical evidences delivered clear evidences so far to substantiate the claim. Against this backdrop, the paper mainly seeks to identify the inter-linkage between the process of democratic decentralization and participation possibilities of the marginalized by focusing on the Adivasis (STs) of rural Kerala. Although there is a strong positive correlation between the reservation of seats and inclusion of tribes in local governments, there is no equity in capturing the new political opportunities by different ethnic tribal groups in Kerala. It has been further attested that, a few socio- economically and politically elite tribal groups cornered the maximum benefit of tribal reservation, and the under privileged and excluded segments gained a little.